Group therapy in transactional analysis : theory through practice - Tangolo, Anna Emanuela; Massi, Anna (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2022)
Tangolo and Massi offer a complete manual for Transactional Analysis-based group therapy. Group Therapy in Transactional Analysis demonstrates the evolution of TA as a relational psychodynamic therapy rich in clinical experiences both within individual and group settings. The authors outline how to select patients, which setting to provide, how to establish contracts and which techniques to use during group sessions. The book includes a full assessment of research and theory, clearly demonstrating efficacy and taking into account neuroscientific studies on intersubjectivity and the social brain. This is combined with a practical approach which supports therapists from the very first steps to the analysis of more complex interpersonal dynamics and dream analysis in a group setting. Finally, future research directions are discussed, together with an overview of an experiment on online groups in the time of coronavirus. This foundational text will be a key reference for therapists in training and professionals new to the principles of Transactional Analysis. It will also be of interest to students on psychotherapy training and clinical psychology courses.
1. Introduction 2. Why the Group 3. Group Theory 4. Change and Empowerment Factors in Group 5. Intersubjectivity and the Group as Emotional Regulator 6. Client Selection and Group Composition 7. Setting 8. Therapeutic Alliance and Contracts 9. Decontamination Work in a Group Setting 10. Deconfusion Work in a Group Setting 11. Basic Techniques: Therapeutic Operations 12. Advanced Techniques 13. Monitoring Group Evolution Through Group Imago Analysis 14. Transference, Countertransference, Games, and Enactments 15. Dreamwork in Group Therapy 16. Efficacy of TA Psychotherapy Groups in the Treatment of Personality Disorders 17. Depressive and Bipolar Disorders in a Group Setting 18. The End of Therapy 19. A Case Study 20. Online Groups at the Time of Coronavirus: An Ongoing Case Study 21. Efficacy and Limits of Group Psychotherapy 22. Appendix
Keywords: PSYCHOLOGY / Mental Health; PSYCHOLOGY / Psychotherapy / Group; Group psychotherapy; Transactional analysis